Correlation of publication frequency with impact factors in 1058 medical journals in SCI-expanded database - Liu Xue, Li; Liu Rui, Yuan; Wang Mei, Ying (Malaysian Journal of Library and Information Science, 2012)
We collected the impact factor (IF) and 5-year impact factor (5-IF) of 1058 medical journals in SCI-expanded database, and explore their changes with the increase of publication frequency (PF). Our studies shows that there are positive correlation of PF with IF (r=0.313, P=0.000) and 5-IF (r=0.298, P=0.000). According to the levels of journals’ PF, the journals were divided into four groups. The journals with PF from 1 to 5 were divided into group I ，t hat from 6 to 11, 12 to 23, 24 to 58 were divided into group II, group III and group IV, respectively. The IF of the journals in group I were 1.94±1.71，2.16±4.30 in group II, 3.17±2.93 in group III, and 8.00±9.68 in group IV, respectively. The 5-IF of the journals in group I were 2.080±1.668，2.194±3.046 in group II, 3.253±3.045 in group III, and 8.00±10.015 in group IV, respectively. With comparison of mean ranks of IF and 5-IF among four groups with different PF, we had found that the higher the PF the higher the IF (H=114.075, P=0.000) and 5-IF (H=102.796, P=0.000). From 2006 to 2008, PF increased at various degrees in 22 journals, of which the total citation increased too, and just 18 journals of which IF increased. After PF increased in 22 journals, IF and 5-year IF were obviously higher than those before PF increased (Z=2.386, P=0.017; Z=4.015, P=0.000). We concluded that the IF and 5-IF are increased with the increasing of journals’ PF. The mechanism of the positive correlation between IF and PF are discussed.